The inscriptions carved on the collar of the Lions fountain in the Red of Granada - serhane, Halim (The Algerian Historical Journal, 2026)
The inscriptions carved on the collar and circumference of the Lions Fountain in the Alhambra are studied within the field of Islamic archeology and arts because of their close connection with the Arab-Islamic civilization in Andalusia during the eighteenth century AH fourteenth century CE . In this perspective, it belongs to what archaeologists call the term "fixed monuments". In studying it, we have adopted the extrapolation of historical information and quoting it from its assumptions, whether it is related to the life and biography of the minister poet Ibn Zamrak, or to the poems carved by diving into the mothers of literary books such as the poetry of the poet, the rest and the aware. We also disassembled these writings, read them, interviewed their texts, and compared them with reliable archaeological sources and documents because it is difficult to challenge them.